Phasing of millennial-scale climate variability in the Pacific and Atlantic Oceans - Walczak, Maureen H.; Mix, Alan C.; Cowan, Ellen A.; Fallon, Stewart; Fifield, L. Keith; Alder, Jay R.; Du, Jianghui; Haley, Brian; Hobern, Tim; Padman, June; Praetorius, Summer K.; Schmittner, Andreas; et al. (Science, 2020)
Calving cousins Walczak et al. report that increases in Pacific Ocean ventilation and periods of rapid production of icebergs from the Cordilleran Ice Sheet during the last glacial period preceded episodic iceberg discharges into the Atlantic Ocean (see the Perspective by Jaeger and Shevenell). Marine sediments from the Gulf of Alaska show that increases in vertical mixing of the ocean there correspond with intense iceberg calving from the ice sheet that covered much of high-latitude western North America and that these changes occurred before the analogous Heinrich events in the North Atlantic. Thus, these Pacific climate system reorganizations may have been an early part of a cascade of dynamic climate events with global repercussions. Science, this issue p. 716; see also p. 662 New radiocarbon and sedimentological results from the Gulf of Alaska document recurrent millennial-scale episodes of reorganized Pacific Ocean ventilation synchronous with rapid Cordilleran Ice Sheet discharge, indicating close coupling of ice-ocean dynamics spanning the past 42,000 years. Ventilation of the intermediate-depth North Pacific tracks strength of the Asian monsoon, supporting a role for moisture and heat transport from low latitudes in North Pacific paleoclimate. Changes in carbon-14 age of intermediate waters are in phase with peaks in Cordilleran ice-rafted debris delivery, and both consistently precede ice discharge events from the Laurentide Ice Sheet, known as Heinrich events. This timing precludes an Atlantic trigger for Cordilleran Ice Sheet retreat and instead implicates the Pacific as an early part of a cascade of dynamic climate events with global impact. Pacific iceberg discharge events preceded their Atlantic counterparts during the last glacial period. Pacific iceberg discharge events preceded their Atlantic counterparts during the last glacial period.